Visit, Revisit, or Stay Longer? A Case of Emerging Tourism Destination - Shahren Ahmad, Zaidi Adruce; Hiram, Ting; Puah, Chin Hong; Lim, Tze Yin; Sherrymina, Kichin (Asia Business Research Corporation Limited, 2021)
Despite substantial extant literature on tourists’ visiting behavior, little is known about the intention to visit, revisit, and stay longer in an emerging destination. Sarawak is an emerging destination that has demonstrated the capability to attract tourists from China. The present study lays the groundwork for the exploration of Chinese tourists’ main motives to visit, revisit, and stay longer in Sarawak based on push and pull factors. A qualitative research design was adopted, following which 355 interviews were conducted over two stages of data collection. All transcriptions were then analyzed using thematic analysis. The findings revealed three categories related to the intention to visit Sarawak, namely “China residents who have not been to Sarawak”, “China residents who have been to Sarawak”, and “China residents who consider having a longer stay in Sarawak”. In addition, the pull and push factors influencing their visiting intention were assessed. This case study offers an explanatory model that informs local stakeholders on the significant motivation factors that attract Chinese tourists to Sarawak. From a managerial standpoint, local agencies, tourism promoters, and marketers could expend more resources to advertise Sarawak’s attractions, such as ethnic food, festivals, multi-cultural heritage, adventures, and nature.